РRINCIPLES OF DESIGNING POND FARMS AND THEIR ENGINEERING LANDSCAPING - Baranovych Л.; Baranovych А. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
Fish is one of the significant and valuable sources of human nutrition. Containing a range of important proteins, carbohydrates, fats, vitamins, and minerals, it is an irreplaceable and valuable food product with strategic importance for the state. Fish pond farms have suffered considerable losses due to military actions. The substantial destruction of infrastructure, constant shelling, and the inability to maintain engineering structures have led to the abandonment of many farms, resulting in fish mortality. To safeguard the population from a shortage of fish products at the state level, the Cabinet of Ministers of Ukraine approved the Strategy for the Development of the Fishery Industry of Ukraine until 2030 and the Operational Action Plan for its implementation in 2023–2025 (Decree No 402-r, May 2, 2023). This document explains the ways to address and regulate the problems currently faced by farm pond fisheries. An important step in solving this problem is the expansion of those farms located in the territory controlled by Ukraine, taking into account and using the latest methods in pond farming planning to ensure the population has access to quality, healthy, and fresh fish products with the export potential. The development of pond fish farming is a crucial component of the state's agricultural policy and a strategically important direction for diversifying agribusiness. This article examines the principles of pond farm design. Pond fish farming encompasses the processes of breeding and raising fish in specially created water bodies, such as lakes, technical reservoirs, peat quarries, and others. It is a complex system that requires careful planning and maintenance to ensure high productivity and the quality of fish products. Recommendations are also provided regarding water supply, water quality, and soil, as well as the principles of engineering improvement of pond fish farms, which largely depend on the biological characteristics of the cultivated fish.